Self-Reported Mental Health and Lifestyle Behaviour During the COVID-19 Pandemic in the Czech Population: Evidence From Two Cross-Sectional Surveys - Andrea Dalecká; Andrea Dalecká; Hana Tomášková; Hana Tomášková; Hana Tomášková; Hana Šlachtová; Hana Šlachtová; Hana Šlachtová; Dagmar Skýbová; Dagmar Skýbová; Ratislav Mad'ar (Frontiers Media S.A., 2022)
Objectives: Evidence of the impact of COVID-19 pandemic on mental and physical health behaviours is limited. This study presents results of two cross-sectional surveys on mental health changes and its consequences on healthy and unhealthy lifestyle behaviours.Methods: An online survey was distributed during Spring 2020 (N = 9,168) and Autumn 2020 (N = 1,042) in the Czech Republic. Differences in mental health observed in both surveys were evaluated using Mann-Whitney test and logistic regressions were used to examine demographic and socio-economic determinants of COVID-19-related mental health issues and resulting healthy and unhealthy lifestyle behaviours.Results: In multivariable models, the youngest individuals, females, people with increased work demands and participants with a reduced personal income due to the COVID-19 pandemic were all negatively associated with self-reported mental health issues (p < 0.05). A worsened quality of sleep, dietary habits, physical activity and unhealthy behaviours were highly associated with affected mental health in the models adjusted for potential covariates (p < 0.05).Conclusion: Taken together, these findings suggest that health promotion strategies directed to individuals who are at risk should be encouraged to adopt and/or maintain positive health-related behaviours.